ARTISTIC REALITY AND ITS FEATURES IN THE WORKS OF V. O. PELEVIN IN SEARCH OF IDENTITY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article proposes to read the book by V. O. Pelevin "Dialectics of the Transitional Period from Nowhere to Nowhere" through intertextual references to the poem by N. V. Gogol "Dead Souls". Modifications of the images of the troika bird and dead souls, as well as references to the facts of the life of the Russian classic are revealed. The identified elements allow us to determine one of the thematic blocks in the book - the theme of the historical path of Russia and the development of society.